Machines, Films, and Operas: A (Mostly) Soviet Perspective - de Castro, Paulo (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2019)
In this article I explore some of the ways in which opera was affected by the dynamics of rupture and experimentation in the Soviet Union in the 1920s and early 1930s. In particular, I examine the criticism of opera as a genre among composers and theatrical practitioners, such as Nikolay Foregger, who advocated a fusion of opera and ballet inspired by the rhythms, movements, and sounds of modernity, and Adrian Piotrovsky, who argued for the transfer of cinematic devices to other art forms, including opera. The article further explores some intersections with the Futurist and Constructivist cult of the machine as reflected in the operatic experiments of Vladimir Deshevov and Aleksandr Mosolov, which were almost immediately suppressed by the rise of a more populist aesthetics and remain largely unknown.